To solve the equation \( x \cdot 4 + y^2 = 48 \), we can rearrange it into the form:
\[ 4x + y^2 = 48 \]
This means we can isolate one of the variables, say \( y^2 \):
\[ y^2 = 48 - 4x \]
Now, the right side must be non-negative since \( y^2 \) cannot be negative. Therefore:
\[ 48 - 4x \geq 0 \]
From this inequality, we can solve for \( x \):
\[ 48 \geq 4x \quad \Rightarrow \quad 12 \geq x \quad \Rightarrow \quad x \leq 12 \]
Now, substituting integer values for \( x \) from 0 to 12 will give us possible values for \( y^2 \):
-
If \( x = 0 \): \[ y^2 = 48 - 4(0) = 48 \quad \Rightarrow \quad y = \pm \sqrt{48} \quad \Rightarrow \quad y = \pm 4\sqrt{3} \]
-
If \( x = 1 \): \[ y^2 = 48 - 4(1) = 44 \quad \Rightarrow \quad y = \pm \sqrt{44} \quad \Rightarrow \quad y = \pm 2\sqrt{11} \]
-
If \( x = 2 \): \[ y^2 = 48 - 4(2) = 40 \quad \Rightarrow \quad y = \pm \sqrt{40} \quad \Rightarrow \quad y = \pm 2\sqrt{10} \]
-
If \( x = 3 \): \[ y^2 = 48 - 4(3) = 36 \quad \Rightarrow \quad y = \pm \sqrt{36} \quad \Rightarrow \quad y = \pm 6 \]
-
If \( x = 4 \): \[ y^2 = 48 - 4(4) = 32 \quad \Rightarrow \quad y = \pm \sqrt{32} \quad \Rightarrow \quad y = \pm 4\sqrt{2} \]
-
If \( x = 5 \): \[ y^2 = 48 - 4(5) = 28 \quad \Rightarrow \quad y = \pm \sqrt{28} \quad \Rightarrow \quad y = \pm 2\sqrt{7} \]
-
If \( x = 6 \): \[ y^2 = 48 - 4(6) = 24 \quad \Rightarrow \quad y = \pm \sqrt{24} \quad \Rightarrow \quad y = \pm 2\sqrt{6} \]
-
If \( x = 7 \): \[ y^2 = 48 - 4(7) = 20 \quad \Rightarrow \quad y = \pm \sqrt{20} \quad \Rightarrow \quad y = \pm 2\sqrt{5} \]
-
If \( x = 8 \): \[ y^2 = 48 - 4(8) = 16 \quad \Rightarrow \quad y = \pm \sqrt{16} \quad \Rightarrow \quad y = \pm 4 \]
-
If \( x = 9 \): \[ y^2 = 48 - 4(9) = 12 \quad \Rightarrow \quad y = \pm \sqrt{12} \quad \Rightarrow \quad y = \pm 2\sqrt{3} \]
-
If \( x = 10 \): \[ y^2 = 48 - 4(10) = 8 \quad \Rightarrow \quad y = \pm \sqrt{8} \quad \Rightarrow \quad y = \pm 2\sqrt{2} \]
-
If \( x = 11 \): \[ y^2 = 48 - 4(11) = 4 \quad \Rightarrow \quad y = \pm \sqrt{4} \quad \Rightarrow \quad y = \pm 2 \]
-
If \( x = 12 \): \[ y^2 = 48 - 4(12) = 0 \quad \Rightarrow \quad y = 0 \]
Thus, we have various pairs of \( (x, y) \) that satisfy the equation. Some notable pairs include:
- \( (3, 6) \)
- \( (8, 4) \)
- \( (11, 2) \)
- \( (12, 0) \)
Would you like to analyze further or clarify anything?